Psychological measures of patient's decision-making for prenatal genetic testing. (2nd November 2022) - Herrera, Kimberly M.; Milone, Gina; Davis, Jay A.; Persad, Malini D.; Dinglas, Cheryl; Heiselman, Cassandra; Buckley, Ayisha; Garretto, Diana; Pastore, Lisa M.
Abstract: Objective: To use a questionnaire to determine the levels of maternal decision-related distress, clarity of the pros and cons, and certainty when considering prenatal genetic diagnostic testing; and to assess the relationship between these constructs and patient characteristics. Method: Cross-sectional study. Voluntary, anonymous questionnaires distributed 2017–2019 to women referred for invasive prenatal genetic testing. Excluded: English or Spanish illiterate. Maternal characteristics were collected. Questions evaluated distress, decisional certainty, and decisional clarity on a 5-point Likert scale (range: 0 = low/uncertain/unclear to 4 = high/certain/clear). Analysis: non-parametric Kruskal–Wallis, correlation statistics, and ANOVA. Results: Forty-four female patients completed it. Most were married, white, Catholic, and multiparous. 58% had already made a testing decision. Patients expressed low distress levels (mean 1.18 ± 0.80) and expressed high decisional certainty (mean 3.28 ± 0.76) and clarity (mean 3.30 ± 0.99). Decisional certainty and clarity were positively correlated ( r = 0.47, p < .01), whereas distress was negatively correlated with decisional certainty ( r = −0.8136, p < .0005) and decisional clarity ( r = −0.49, p = .007). No significant differences by religion or parity. Greater distress ( p < .05) and less decisional clarity ( p = .07) occurred between those still debating testing vs those who had decided. Conclusions: Higher maternal distress scores were associated with lower decisional certainty and decisional clarity in women considering prenatal genetic testing.